Beyond Appearance: A New Look at Adolescent Girls. 1999
DOI: 10.1037/10325-005
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant adolescent girls of color: Facing American challenges.

Abstract: A major task of adolescence is the development of a personal identity; events and experiences occurring during that period have enormous power in shaping the developing identity. Adolescents' relative receptivity to the impact of social events, filtered through their families, is mediated by their life stage and has an impact on their individual personality development, including their values, expectations about the world, and themselves (Stewart & Healy, 1989). Ethnic heritage is another powerful influence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Research has consistently shown that the ability to adapt to life in the USA while retaining one's cultural heritage is essential for successful acculturation and may increase the chances of success in school (De las Fuentes & Vasquez 1999; Castro et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently shown that the ability to adapt to life in the USA while retaining one's cultural heritage is essential for successful acculturation and may increase the chances of success in school (De las Fuentes & Vasquez 1999; Castro et al. 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For immigrant youth, this task can be particularly challenging considering the multiple worlds they traverse and live in and the contradictions between the host culture and their native culture and discrimination from the host society ( e.g. , Aronowitz, 1984; Vigil, 1988; Grinberg and Grinberg, 1990; Kohatsu, Suzuki, and Bennett, 1991; Goodenow and Espin, 1993; Phelan, Davidson, and Yu, 1993; Florsheim, 1997; Phinney and Landin, 1998; De Las Fuentes and Vasquez, 1999; Suárez‐Orozco, 2000, 2001; Talbani and Hasanali, 2000). When there is too much cultural dissonance, when cultural guides are inadequate, and when the social mirror reflects negative images, adolescents may find it difficult to develop a flexible and adaptive sense of self.…”
Section: Migration and Gender Scholarship In The Field Of Psychologymentioning
confidence: 99%
“…For many girls, bridging the different cultures can be very challenging during adolescence, because of the inherent cultural clashes and conflicts between the American culture and their home culture ( e.g. , Sue and Sue, 1973; Kim, 1981; Sung, 1987, 1985; Rosenthal and Feldman, 1992; Goodenow and Espin, 1993; Uba, 1994; Waters, 1996; Florsheim, 1997; De Las Fuentes, 1999). Ginorio and Huston (2001) in their AAUW report of Latinas in education found that many Latina girls experienced a “bifurcated self” due to the centrality of family and religion in their lives and the varied expectations of school and peer groups.…”
mentioning
confidence: 99%
“…The research on voice is in its infancy, particularly as it relates to diverse populations, and counselors need to use multiple lenses to interpret recent research findings and how they might apply to girls across cultures. As de las Fuentes and Vasquez (1999) noted, "ethnic heritage is a powerful influence in determining one's identity as it is an important factor in developing a sense of belonging as well as contributing to issues of inclusion and exclusion" (p. 131).…”
mentioning
confidence: 99%